2020
DOI: 10.1038/s41598-020-75793-0
|View full text |Cite
|
Sign up to set email alerts
|

Dough rheology, antioxidants, textural, physicochemical characteristics, and sensory quality of pizza base enriched with onion (Allium cepa L.) skin powder

Abstract: In the present research, wheat flour was replaced with onion skin powder (OSP) in 2%, 3.5%, and 5% concentration along with control to produce different pizza base variants. Prepared pizza doughs and base were investigated for different quality parameters. Rheology revealed that increased concentration of OSP elevated the storage modulus (G’) (solid nature) of pizza doughs. Colour measurement of both the doughs and pizza base exhibited lightness in control (L* 86.46 ± 0.39) and darkness in 5% OSP variant (L* 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Pizza has been the object of several investigations aimed at improving its nutritional features [ 10 , 11 , 12 , 13 ], without neglecting gluten-free versions [ 14 , 15 ], but very few studies are available on focaccia . The reformulation of focaccia using Apulian black chickpea flour, which provides anthocyanins and increases antioxidant activity, was investigated by Pasqualone et al [ 12 ], while Delcuratolo et al [ 16 , 17 ] evaluated the role of focaccia toppings on the oxidation stability and content of polar compounds arising from triacylglycerol oxidation and hydrolysis, which are responsible for negative health implications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pizza has been the object of several investigations aimed at improving its nutritional features [ 10 , 11 , 12 , 13 ], without neglecting gluten-free versions [ 14 , 15 ], but very few studies are available on focaccia . The reformulation of focaccia using Apulian black chickpea flour, which provides anthocyanins and increases antioxidant activity, was investigated by Pasqualone et al [ 12 ], while Delcuratolo et al [ 16 , 17 ] evaluated the role of focaccia toppings on the oxidation stability and content of polar compounds arising from triacylglycerol oxidation and hydrolysis, which are responsible for negative health implications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well-known that the palatability of food items may be influenced by the kind of food, the amount of added fiber and its physiochemical properties, the food texture and its organoleptic properties as demonstrated in previous studies (31)(32)(33)(34). In our study, the participants could select from a variety of fiber-enriched products.…”
Section: Discussionmentioning
confidence: 92%
“…FTIR analysis suggested that all the cultivars were rich in various functional groups, such as methylene in the saturated aliphatic group, aromatic ring, carbohydrate, and sulphur oxy compounds. Onion skin waste in processing industries may be utilized for various purposes like functional/nutraceutical food development, energy, and biogas production [5][6][7]10].…”
Section: Discussionmentioning
confidence: 99%
“…Onion flavonoids also show antiproliferative activity that can degrade excess polyamine concentration in the body [6]. Hence, onion skin powder may be incorporated into bakery products and bread which are good sources of energy and consumed widely as well [7]. Wheat bread was fortified with the addition of 3% onion skin and it enhanced the antioxidant property of the bread with sensory acceptance [8].…”
Section: Introductionmentioning
confidence: 99%